SÍNTESE, CARACTERIZAÇÃO E ESTUDO CONFORMACIONAL DO N-ACETILASPARTATO DE DIMETILA E COMPOSTOS CORRELATOS - Costin, Taíssa Adriana (2013)
Due to the great importance of the aspartic acid, since it is found in the Dimethyl N-acetylaspartate in high concentrations in the urine of patients with different neurological problems, an example is Canavan disease, which has been associated with elevated concentrations of N-acetylaspartate in cerebrospinal fluid, it inspired the interest of studying conformational equilibrium of compounds with structures similar to Dimethyl N-Acetylaspartate. The focus of this study was to research the compound structural Dimethyl N-acetylaspartate (NAA) and their derivatives Dimethyl N-Methylaspartate (NMA) and Dimethyl N, N- Dimethylaspartate (NDA). The principle was to establish the most stable geometries and populations of conformers involved in the equilibrium phase and isolated in solution. To perform DFT calculations, we used the Gaussian 03 software package. The potential energy surfaces (SEPs) were obtained with B3LYP/6-311G level of theory and the points of lowest energy, made possible as more stable geometries which were optimized with the level of theory B3LYP/cc-PVTZ. For the structure of the NAA, we found seven more stable geometries. The majority conformer of NAA showed a population of 31,9% on balance. For the structure of the NMA met ten most stable geometries. The majority conformer population showed a 35,4% on the balance. As for the structure of the NDA, it also met seven most stable geometries. The majority conformer population showed a 46,5% on the balance. Besides the equilibrium phase alone was evaluated with these structures and solvation calculations it was observed that populations of conformers were changed, but the same major conformer being isolated majority remained in solution. In order to compare the theoretical data with experimental data, these compounds were synthesized therefore performed NMR spectroscopic analysis which analyzed the coupling constants 2J and 3J and IV, held the deconvolution of the carbonyl band.